Unveiling the Nexus of Digital Transformation and Change Management: A Pioneering Bibliometric Analysis - Pallavi Singh; Rinki joshi; Prachi Pathak; Vaishali Aswal (STIE Malangkucecwara, 2026)
As the digital market grows, businesses must embrace digital transformation (DT) to remain competitive. The integration of digital technologies has redefined business operations, models, and customer engagement. However, successful DT is not solely a technological initiative—it requires robust change management (CM) to address resistance, enhance organisational agility, and ensure long-term sustainability. This study presents the first bibliometric analysis to explore the intersection of DT and CM, offering a comprehensive view of how scholarship in these domains has evolved. Using VOSviewer and Biblioshiny, we conduct co-citation and co-occurrence mapping to identify influential studies, emerging trends, and persistent research gaps. Scopus was chosen as the primary database for material processing, given its extensive coverage of peer-reviewed literature across disciplines. In addition, data sources such as surveys, databases, and digital archives were integrated to provide valuable insights and contextual depth, ensuring a more nuanced and holistic analysis. The findings highlight the growing importance of DT and underscore the critical role of leadership, skill development, and effective technology implementation in driving change. Our study reveals that research in this area increasingly emphasizes the integration of technology with management practices and employee engagement. By combining bibliometric analysis with diverse data sources, this article not only maps the trajectory of DT and CM research but also identifies opportunities for future investigation. Ultimately, the study calls for a comprehensive approach that blends technological innovation, managerial processes, and workforce adaptability to help organisations thrive in an era of rapid digital change.